Dinamika flourishing pada guru di Yayasan Pembinaan Anak Cacat (YPAC) Palembang - Amanda, Zarnalia; Lukmawati (Universitas Muhammadiyah Malang, 2026)
This study aims to examine the dynamics of flourishing among teachers at YPAC Palembang, including its characteristics, influencing factors, and impacts on teachers’ personal and professional lives. A qualitative, phenomenological design was employed to explore teachers’ lived experiences of flourishing. Data were collected through in-depth interviews and participant observation involving (n = 3) teachersselected through purposive sampling. The findings indicate that flourishing among teachers is characterized by gratitude, a strong sense of meaning in their work, positive social connectedness, and the ability to develop personal potential despite various limitations and challenges. Factors influencing flourishing include social support from colleagues and family, religiosity, an inclusive work environment, and intrinsic motivation in fulfilling their roles as educators. The impacts of flourishing are reflected in increased life satisfaction, emotionalstability, harmonious social relationships, and improved teaching quality and professional commitment. This study concludes that flourishing among teachers is a dynamic process involving a balance between personal, social, and professional aspects that interact and reinforce one another. These findings highlight the importance of creating supportive and inclusive educational environments to promoteteacher well-being and optimal performance, particularly in inclusive education settings.